Knowledge domain and hotspots analysis concerning applications of two-photon polymerization in biomedical field: A bibliometric and visualized study - Fu, Hongxun; Jing, Xian; Lin, Jieqiong; Wang, Liye; Jiang, Hancheng; Yu, Baojun; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Two-photon polymerization (TPP) utilizes an optical nonlinear absorption process to initiate the polymerization of photopolymerizable materials. To date, it is the only technique capable of fabricating complex 3D microstructures with finely adjusted geometry on the cell and sub-cell scales. TPP shows a very promising potential in biomedical applications related to high-resolution features, including drug delivery, tissue engineering, microfluidic devices, and so forth. Therefore, it is of high significance to grasp the global scientific achievements in this field. An analysis of publications concerning the applications of TPP in the biomedical field was performed, and the knowledge domain, research hotspots, frontiers, and research directions in this topic were identified according to the research results. Methods: The publications concerning TPP applications in biomedical field were retrieved from WoSCC between 2003 and 2022, Bibliometrics and visual analysis employing CiteSpace software and R-language package Bibliometrix were performed in this study. Results: A total of 415 publications regarding the TPP applications in the biomedical field were retrieved from WoSCC, including 377 articles, and 38 review articles. The studies pertaining to the biomedical applications of TPP began back in 2003 and showed an upward trend constantly. Especially in the recent 5 years, studies of TPP in biomedical field have increased rapidly, with the number of publications from 2017 to 2021 accounting for 52.29% of the total. In terms of output, China was the leading country and Chinese Acad Sci, Tech Inst Phys and Chem was the leading institution. The United States showed the closest cooperation with other countries. ACS applied materials and interfaces was the most prolific journal (n = 13), followed by Biofabrication (n = 11) and Optics express (n = 10). The journals having the top cited papers were Biomaterials, Advanced materials, and Applied physic letters. The most productive author was Aleksandr Ovsianikov (27 articles). Meanwhile, researchers who had close cooperation with other researchers were also prolific authors. “cell behavior”, " (tissue engineering) scaffolds”, “biomaterials,” and “hydrogel” were the main co-occurrence keywords and “additional manufacturing”, “3D printing,” and “microstructures” were the recent burst keywords. The Keyword clusters, “stem cells,” and “mucosal delivery”, appeared recently. A paper reporting unprecedented high-resolution bull models fabricated by TPP was the most locally cited reference (cited 60 times). “Magnetic actuation” and “additive manufacturing” were recently co-cited reference clusters and an article concerning ultracompact compound lens systems manufactured by TPP was the latest burst reference. Conclusion: The applications of TPP in biomedical field is an interdisciplinary research topic and the development of this field requires the active collaboration of researchers and experts from all relevant disciplines. Bringing up a better utilization of TPP as an additive manufacturing technology to better serve the biomedical development has always been the research focus in this field. Research on stem cells behaviors and mucosal delivery based on microstructures fabricated using TPP were becoming new hotspots. And it can be predicted that using TPP as a sourcing technique to fabricate biomedical-related structures and devices is a new research direction. In addition, the research of functional polymers, such as magnetic-driven polymers, was the frontier topic of TPP biomedical applications.